The Microbiome and Cancer: Implications for Oncology Nursing Science. Issue 3 (May 2016) - Kelly, Debra Lynch; Lyon, Debra E.; Yoon, Saunjoo L.; Horgas, Ann L.
Abstract : Background: Approximately 1.6 million Americans were diagnosed with cancer in 2014. To combat their disease, many individuals received either curative or palliative treatments that produced undesired symptoms. These symptoms, which often cause significant distress for individuals coping with cancer, may share biologic underpinnings such as epigenetic changes and immune dysregulation. Alterations in the normal flora of the gut may also influence cancer symptoms. Objective: The aim of this review is to describe the emerging role for the gut microbiome in cancer research, especially the potential relationship between the gut microbiome and cancer symptoms. Methods: Extant literature was reviewed and synthesized. Results: The majority of studies linking the gut microbiota and cancer are animal models and focus on the relationship between dysbiosis and colorectal cancer. Emerging evidence supports that the "gut-brain" connection is a plausible mechanism for "psychoneurological" cancer symptoms such as depression, pain, and fatigue. Conclusions: There is compelling evidence that the gut microbiota affects cancer via several mechanisms, including microbial diversity and number, metabolism, and/or immune initiation. However, more research is necessary to elucidate these mechanisms, particularly among a variety of cancers and cancer-related symptoms. Implications for Practice: A better understanding of the role of the gut microbiota in cancer symptoms may lead to the development of targeted individualized interventions affecting the gut microbiota that prevent or ameliorate dysbiosis, thereby reducing symptoms. These interventions may emphasize self-care management strategies essential for wellness, such as diet, nutrition, and stress reduction.